1983
DOI: 10.3109/01485018308987453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Silver Staining Patterns of Water Buffalo, Goat, and Pig Spermatozoa

Abstract: from river and swamp water buffalo (Bubalus bubalis), goat, and pig were stained using a silver nitrate procedure and examined under bright field optics. The silver nitrate differentiated many detailed morphologic features of the head, midpiece, and tail of spermatozoa between the species studied. Acrosomal integrity due to sperm injury or aging and various sperm abnormalities were also clearly identified by silver nitrate. Silver staining patterns revealed species-specific and strain-specific differences, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The use of this technique helps to reveal more details in the morphological structure of spermatozoa than the methods using acidic dyes (1). Additionally, this method makes it possible to clearly observe differences in the integrity of the acrosome (thanks to the possibility of observing numerous details in its structure), which can result from damage, ageing processes, or various kinds of semen anomalies (4). As regards the standard semen assessment, there is a perceptible lack of clearly formulated conventional semen parameters that would allow an effective evaluation of fertilisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of this technique helps to reveal more details in the morphological structure of spermatozoa than the methods using acidic dyes (1). Additionally, this method makes it possible to clearly observe differences in the integrity of the acrosome (thanks to the possibility of observing numerous details in its structure), which can result from damage, ageing processes, or various kinds of semen anomalies (4). As regards the standard semen assessment, there is a perceptible lack of clearly formulated conventional semen parameters that would allow an effective evaluation of fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used for the assessment of fresh spermatozoa from a smear and fixed sample. Various authors have concluded that it can be used in biological studies and assessments of semen for artificial insemination (1,4). It can be assumed that the use of the technique in semen analyses can provide detailed information concerning the morphological structure and morphometric dimensions of spermatozoa, as these aspects are gaining more importance in studies on fertility and preservation techniques for semen to be used for artificial insemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver-stainability of cytoplasmic structures, including the nuclear and acrosomal ring and the postacrosoma1 sheath, has been described in spermatids of several mammalian species (Gresson and Zlotnik, 1945;Elder and Hsu, 1982;Czaker, 1985b,c;Sousa and Azevedo, 1992) and in a species-specific pattern in mature spermatozoa (Elder and Hsu, 1981;Bongso, 1983;Flaherty, 1987;Curry et al, 1989;Van-der-Horst et al, 1991). The physical and biochemical properties of the argentophilic substance at different stages of sperm development have, however, yet to be ascertained.…”
mentioning
confidence: 99%
“…Postmeiotically, silver-stainable nucleolar substance has been shown to abolish after prophase pachytene, reappear in the first stages of spermiogenesis, but to disappear once more during the elongation phase (Hofgartner et al, 1979;Ironside and 1979; Schmid et al, 1982, 1983, Mirre and Knibiehler, 1985Lunghi et al, 1987;Dadoune et al, 1991).…”
mentioning
confidence: 99%